The Convention on the Rights of the Child - United Nations (United Nations, 2019)
Thirty years ago, world leaders made a historic commitment to the world’s children by adopting the United Nations Convention on the Rights of the Child. This Convention, one of the core human rights instruments, has become the most widely ratified human rights treaty in history and has helped transform children’s lives around the world. But still not every child gets to enjoy a full childhood. Still, too many childhoods are cut short. It is up to our generation to demand that governments, businesses and communities fulfil their commitments and take action for child rights now, once and for all. They must commit to making sure every child, has every right. This book is published to commemorate this momentous anniversary.